If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 4b = 2 + 2b Solving 8 + 4b = 2 + 2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2b' to each side of the equation. 8 + 4b + -2b = 2 + 2b + -2b Combine like terms: 4b + -2b = 2b 8 + 2b = 2 + 2b + -2b Combine like terms: 2b + -2b = 0 8 + 2b = 2 + 0 8 + 2b = 2 Add '-8' to each side of the equation. 8 + -8 + 2b = 2 + -8 Combine like terms: 8 + -8 = 0 0 + 2b = 2 + -8 2b = 2 + -8 Combine like terms: 2 + -8 = -6 2b = -6 Divide each side by '2'. b = -3 Simplifying b = -3
| 7-x=-5x-1 | | x^4+8x^3+8x^2+7=0 | | 2x+11=-11 | | G=tm | | 6-4w=39+7w | | 9y+17=24 | | 7(x+9)-3=2(x+9)+17 | | T=9+6b | | -0.57=15h+16.23 | | 8(n-1)-2n=-2(-4n+2) | | 8(n-1)-2=-2(-4n+2) | | 10=2c+22 | | 5(3-t)-(3-3t)=3 | | -23+x=x+30 | | 1=-4z+21 | | 3(3+5x)-5=34 | | 8(n-1)=-2(-4n+2) | | 18-x=15 | | 5x-3(2x+3)=-2x-3 | | 240=5(7m+6) | | -8c-12=36 | | 16(6)+24=-18+9(6) | | 3m+2=14 | | 3x+6=.78 | | 2(d-4)=-2 | | 4.3(x)=28.81 | | 7(x-5)=56 | | 9=12x-7 | | x^2-50=0 | | 13+12x=-6x+49 | | 2[2x-2]=12 | | 12.4+2a=5a+5.5 |